A systematic review of atopic dermatitis - pathomechanism, diagnosis and topical treatment - Osiński, Damian; Kawa, Zuzanna; Kasprzak, Maria; Jędrzejewska, Aleksandra; Jureczko, Aleksandra; Kleczaj, Klaudia; Levadna, Valentyna; Jaworowska, Julia; Babiarz, Gabriela; Kanarszczuk, Julia (Quality in Sport, 2025)
Introduction: Atopic dermatitis (AD), also known as eczema, is a chronic, recurrent inflammatory skin disease characterized by dryness, itching and rashes. It is one of the most common dermatological diseases, affecting both children and adults. The pathogenesis of AD is complex and involves a defect in the epidermal barrier, immune system dysfunction and changes in the composition of the skin microbiota. Various therapeutic approaches are used to treat AD, including skin moisturizers, glucocorticosteroids, topical calcineurin inhibitors, PDE-4 inhibitors, JAK inhibitors, and phototherapy. The increasing number of AD cases is a serious medical problem that affects not only dermatology and allergology, but also pediatrics and family medicine. AD therapy should effectively eliminate the symptoms of the disease, prevent exacerbations, complications, and improve patients’ quality of life. [1,2,3,4] Research objective: The objective of this study is to review the literature on atopic dermatitis, its pathomechanism, and the difficulties associated with its diagnosis and treatment. Conclusions: Atopic dermatitis is a chronic skin disease with complex pathogenesis, involving epidermal barrier defect, immune disorders, and microbiota dysbiosis. Diagnosis is based on clinical presentation and severity scales, as there are no specific biomarkers. Patient education, elimination of exacerbating factors and individualization of therapy are key. Modern medications and educational programs improve patients’ quality of life and allow for better disease control. Continuous research will allow for a better understanding of the pathophysiology of atopic dermatitis and the development of effective therapeutic strategies that can contribute to long-term control of the disease.